Surgimiento de las prácticas científicas de colaboración en la ciencia mexicana con cobertura en los índices internacionales (2010)
ABSTRACT: A study of mainstream Mexican scientific production from 1900 to 1950 is presented. A methodological mixture is made with historiographical and bibliometrical network analysis elements. This is presented in order to characterize the evolution of scientific practices. Articles are taken from Science Citation Index and SCOPUS and they are analized through co-authorship networks. Analysis and contrast between historical facts of scientific organization and cohesion, centrality and density measures of co-authorship networks show an enrichment and diversification of Mexican science organization. This demonstrates a consolidation stage between 1930 and 1950 in this country.